The Effectiveness of Spiritual Interventions in Improving the Mental Health of Patients Receiving Hemodialysis Treatment in Nursing Care: A Meta-Analysis Study - Mine Ekinci; Ayşe Okanlı; Ömer Taşçı; Mustafa Durmuş (Atatürk University, 2024)
Objective: The aim of this study is to investigate the relationship between spiritual well-being and anxiety and depression in patients receiving hemodialysis treatment through meta-analysis method.Methods: Pubmed, the Cochrane Central Register of Controlled Trials (CENTRAL), Web of Science, EBSCOhost, and ProQuest databases were used to gather the data. All databases were reviewed for the last time on April 5, 2022, and a total of 5 studies were included in this meta-analysis. Effect size was evaluated according to Cohen's r correlation coefficient effect width classification. I2 tests were calculated to test heterogeneity.Results: It was found that the effect of spirituality on reducing depression was negative and at a large effect level. Moreover, it was investigated that the effect of spiritual well-being on reducing anxiety was negative and moderate. Since I2 > 50 in both analyses, random effects model was used for carrying out the process of analysis.Conclusion: It was found that spiritual well-being had a great effect on depression and moderate effect on anxiety in patients receiving hemodialysis treatment. High levels of spiritual well-being can reduce the incidence of anxiety and depression in hemodialysis patients. In addition, it can be indicated that spiritual care offered to patients receiving hemodialysis treatment would reduce the level of anxiety and depression.